2003
DOI: 10.1074/jbc.m309348200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Akt Signaling Is an Early Pro-survival Response That Reflects N-Methyl-D-aspartate Receptor Activation in Huntington's Disease Knock-in Striatal Cells

Abstract: Huntington's disease features the loss of striatal neurons that stems from a disease process that is initiated by mutant huntingtin. Early events in the disease cascade, which predate overt pathology in Hdh CAG knock-in mouse striatum, implicate enhanced N-methyl-D-aspartate (NMDA) receptor activation, with excitotoxity caused by aberrant Ca 2؉ influx. Here we demonstrate in precise genetic Huntington's disease mouse and striatal cell models that these early phenotypes are associated with activation of the Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
111
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 28 publications
(33 reference statements)
17
111
1
Order By: Relevance
“…Corroborating our study, p-(Ser473)Akt/Akt levels were significant decreased in STHdh Q111/Q111 cells [76], in HEK293 cells expressing mHtt with 68 CAG repeats [77] and in HD patient's lymphoblasts and lymphocytes [75]. Akt activation is an early pro-survival striatal response in knock-in Hdh Q111 mice and STHdh Q111/Q111 cells [28]; importantly, activation of IGF-1/Akt pathway caused Htt phosphorylation at Ser421, decreasing mHtt nuclear inclusions and mHtt toxicity [27] and regulated anterograde and retrograde transport defects in HD cortical neurons [78]. Another study demonstrated that p-(Ser473)Akt was unchanged in YAC128 and in R6/2 HD mice, but the levels of p-(Ser421)Htt were decreased in the striatum of YAC128 mice and in cells expressing mHtt [79].…”
Section: Discussionsupporting
confidence: 82%
“…Corroborating our study, p-(Ser473)Akt/Akt levels were significant decreased in STHdh Q111/Q111 cells [76], in HEK293 cells expressing mHtt with 68 CAG repeats [77] and in HD patient's lymphoblasts and lymphocytes [75]. Akt activation is an early pro-survival striatal response in knock-in Hdh Q111 mice and STHdh Q111/Q111 cells [28]; importantly, activation of IGF-1/Akt pathway caused Htt phosphorylation at Ser421, decreasing mHtt nuclear inclusions and mHtt toxicity [27] and regulated anterograde and retrograde transport defects in HD cortical neurons [78]. Another study demonstrated that p-(Ser473)Akt was unchanged in YAC128 and in R6/2 HD mice, but the levels of p-(Ser421)Htt were decreased in the striatum of YAC128 mice and in cells expressing mHtt [79].…”
Section: Discussionsupporting
confidence: 82%
“…To investigate whether altered PHLPP1 levels could be responsible for the previously reported accumulation of pAkt (Ser473) in knock-in HD models, 12 we looked at PHLPP1 protein levels in wild-type (STHdh Q7/Q7 ) and mutant (STHdh Q111/Q111 ) striatal cells, and in the striatum of 5-month-old wild-type (Hdh Q7/Q7 ) and mutant (Hdh Q111/Q111 ) knock-in mice. As shown in Figure 1, PHLPP1 protein levels were decreased in both STHdh Q111/Q111 cells and Hdh Q111/Q111 mouse striatum compared with their respective controls.…”
Section: Resultsmentioning
confidence: 99%
“…12 Thus, we next assessed whether reduced PHLPP1 protein levels in STHdh Q111/Q111 cells could affect the rate of Akt dephosphorylation when the activation signal is blocked. To this end, we treated STHdh Q7/Q7 and STHdh Q111/Q111 cells with wortmannin, a PI3K inhibitor, and pAkt (Ser473) levels were assessed at different time points.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations